Maximum Principle for Solution of Biharmonic Equation in The Ball - Younso, Abd Elbasset; Hanouneh, Ibrahim (Latakia University Journal -Basic Sciences Series, 2019)
The intention of this paper is to estimate the biharmonic equation on a bounded domain in the space for with the boundary condition: where we made a function that equivalent the solution of biharmonic equation: by using and applying the principle of the maximum and minimum value, we can estimate the solution of biharmonic equation through the boundary value : where is a continuous function , Laplace operator , biharmonic operator , is the boundary of the domain , is the derivative for the outward rhyming on the boundary of , , and is Nabla’s operator.